Otolith Growth Rings Pattern In Puntius hexazona From The Streams In The Riau University Area and In The Upstream Of The Sibam River - Salsabila, Izzaty; Windarti, Windarti; M. Putra, Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
Abstract P.hexazonacan be found in the upstream of the Sibam River and in the streams around the Riau University.A study aims to understand the pattern of otolith growth rings has been conducted from July to August 2019.The fish was capture using ascoop net. There were 62 fishes (25 fishes from the upstream of the Sibam River and 37 fishes from the streams in the Riau University). The otoliths (sagita) were removed and manually shaved. Growth rings pattern was studied using a binocular microscope. The distance between the nucleus and the first dark ring was varied, in the fish from the upstream of the Sibam River was 0.1-0.24mm and that of the fish from the stream in the Riau University was 0.9-0.24 mm.The maximum number of the dark ring in the otolith was 2. These data shown that the dark rings are formed individually and was not formed by periodic event in the life of the sumatra fish. The fish from the streams in the Riau University may grow better than the fish that live in the upstream of the Sibam River. Keywords :Dark Ring, Growth Pattern, Sagita, Tiger Fish